Hidayatullah.com and Liputanislam.com Editorial Policies in Middle East Conflict Reporting - Nafisah Zahra; Rachmat Kriyantono; Bambang Dwi Prasetyo (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
Online media has been widely used as a media for jihad by Islamic activists around the world, including in Indonesia. These media include HIdayatullah.com and Liputanislam.com. The two media reported on the conflict that occurred in the Middle East. In this study, researchers used the theory of message content hierarchy in the Shoemaker & Reese mass media. Based on the explanation above, this study aims to find out how the theory of influence hierarchy is applied in determining the production of news about the Middle East conflict in the online media Liputanislam.com and Hidayatullah.com. Researchers use the post-positivism paradigm as a research approach. The research method used in this study is descriptive analysis. The data collection method in this study was interviews with the editors of Liputanislam.com, news writers of Liputanislam.com, and editors of Hidayatullah.com. The results of the study show that there are similarities and differences in the editorial policies of Liputanislam.com and Hidayatullah.com in reporting on Middle East conflicts. The similarities lie at the individual and ideological levels. At the individual level, both news writers for Liputanislam.com and Hidayatullah.com have foreign language skills, namely English and Arabic. At the ideological level, the editors of Liputanislam.com and Hidayatullah.com believe that the mainstream media in Indonesia needs to be more balanced and make many mistakes in publishing news about the Middle East conflict. Meanwhile, the difference is at the organizational and extramedia levels. At the organizational level, Liputanislam.com media workers are given more freedom in choosing news sources than Hidayatullah.com media workers. For the extramedia level, Hidayatullah.com editors tend to choose news sources from authoritative media or official news sites and news agencies owned by Middle Eastern countries. On the other hand, the editorial staff of Liputanislam.com refers to media they think share the same ideology and ideals.